A new species and first record of the subgenus Forcipomyia (Schizoforcipomyia) Chan & LeRoux from the Neotropical Region (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2004)
The biting midge, Forcipomyia (Schizoforcipomyia) harpa n. sp., is described from adult males and females which are apparently restricted to high elevations in the Talamanca Mountains of Costa Rica. The new species represents the first record of the subgenus from the Neotropical Region. Thirteen species of Forcipomyia (Schizoforcipomyia) are now known worldwide.